Anticoagulation approach in morbid obesity: a comprehensive review on venous thromboembolism management - Sorodoc, Victorita; Asaftei, Andreea; Ceasovschih, Alexandr; Lionte, Catalina; Crisan, Simina; Constantin, Mihai; Indrei, Lucia; Sorodoc, Laurentiu (Frontiers in Pharmacology, 2024)
Obesity is a recognized risk factor for venous thromboembolism (VTE), associated with distinct challenges in managing anticoagulation therapy. There is still limited evidence regarding the impact of extreme body weight on the pharmacokinetics, pharmacodynamics, efficacy, and safety of various anticoagulant medications. To our knowledge, this is the first comprehensive review to address both prophylactic and therapeutic anticoagulant dosages specifically for managing VTE in patients with a body mass index (BMI) ≥40 kg/m2 or weight ≥120 kg. Our aim was to synthesize the findings of relevant studies alongside the latest recommendations on anticoagulation in this unique population. We gathered and analyzed data on all classes of anticoagulants available for VTE management, including vitamin K antagonists (VKAs), unfractionated heparin (UFH), low-molecular-weight heparin (LMWH), fondaparinux, and direct oral anticoagulants (DOACs), offering insights into their efficacy and safety profiles. Additionally, we explored special subpopulations of morbidly obese patients, such as those with cancer, renal dysfunction, or those undergoing bariatric surgery, recognizing the nuanced therapeutic challenges they present. The current evidence for anticoagulant therapy in morbidly obese patients with VTE is evidently insufficient, underscoring the need for a tailored approach and meticulous monitoring to achieve an optimal therapeutic balance.